Methodological Principles of Media Technologies’ Influence on Human Being and Geopolitical Processes - Kutsyk, Andrii (Communication Today, 2024)
This article is focused on the conceptualisation of the methodological foundations of the anthropological dimension of the communicative space of media and communication technologies. This text examines various approaches and concepts with the help of which the problems of new communication technologies, in particular social networking sites and messengers, are currently being investigated. The article emphasises that the research methodology of media communication technologies is based and develops in the dimension of an interdisciplinary strategy, which involves the synthesis of philosophical-anthropological, media-philosophical and socio-philosophical approaches, which enables a complex and multifaceted study of the relationships and mutual influences between media technologies and development of personality and social practices, political and geopolitical processes.